Prevalence of Risk Factors of non-communicable Diseases in an Adult Population of Rural Bangladesh - Banik, Palash Chandra; Zaman, M Mostafa; Ahmed, Jasimuddin; Choudhury, Sohel Reza; Moniruzzaman, Mohammad (Cardiovascular Journal, 2018)
Background:A community based survey was carried out to determine the distribution of major noncommunicable diseases risk factors as well as to explore the detection and treatment rate of diabetes mellitus and hypertension in rural adult population of Bangladesh. Methods: The survey was done in2006 among 545 individualsaged 25 to 64 years randomly drawn from a village (Ekhlaspur under Chandpur district) of Bangladesh. Information on diet, physical activity, alcohol and tobacco, and treatment history for hypertension and diabetes were collected. Height, weight, waist circumference, blood pressure, capillary blood glucose and total cholesterol were measured. Results: There were 269 men and 276 women with the mean age of 43.9 years (standard deviation, 11.6 years). Six in ten (62.4%) of them used tobacco in some form (smoking or smokeless), 93.7% did not consume adequate fruits and vegetables (five servings or more), and 7.4% of them had low physical activity. More than 6% were overweight or obese (BMI ≥25kg/m2) and 10% had hypertension (blood pressure ≥140/ 90 mmHg or medication). Capillary blood measurement and history of medication combined provided a prevalence of 3.1% for diabetes while prevalence of hypercholesterolemia (≥240 mg/dL) was 2.9% based on capillary blood cholesterol level alone. Less than half of hypertensive and less than one-tenth diabetes subjects were receiving treatmentfor their respective conditions. Conclusions: Prevalence of noncommunicable diseases risk factorsis fairly high even in thisruralBangladeshi sample. Treatment rate for hypertension and diabetes is quite low. Interventionsshould address lifestyle changes and treatment of diabetes and hypertension. Cardiovasc. j. 2018; 10(2): 126-134